2017
DOI: 10.3758/s13421-017-0750-z
|View full text |Cite
|
Sign up to set email alerts
|

Causal explanation improves judgment under uncertainty, but rarely in a Bayesian way

Abstract: Three studies reexamined the claim that clarifying the causal origin of key statistics can increase normative performance on Bayesian problems involving judgment under uncertainty. Experiments 1 and 2 found that causal explanation did not increase the rate of normative solutions. However, certain types of causal explanation did lead to a reduction in the magnitude of errors in probability estimation. This effect was most pronounced when problem statistics were expressed in percentage formats. Experiment 3 used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…According to this study, errors in observed diagnostic inferences can often be explained by variations in underlying causal models. Hayes et al (2018) suggested that the role of causal models in normative judgments merits further study. The authors were interested in assessing whether representations of causal models facilitate Bayesian probabilistic judgments in terms of normative accuracy as well as reduction in error magnitude.…”
Section: Diagnostic and Predictive Causal Reasoningmentioning
confidence: 99%
“…According to this study, errors in observed diagnostic inferences can often be explained by variations in underlying causal models. Hayes et al (2018) suggested that the role of causal models in normative judgments merits further study. The authors were interested in assessing whether representations of causal models facilitate Bayesian probabilistic judgments in terms of normative accuracy as well as reduction in error magnitude.…”
Section: Diagnostic and Predictive Causal Reasoningmentioning
confidence: 99%